2016
DOI: 10.18544/ep-01.15.01.1634
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation the concentration of selected markers of the atherosclerosis process in children with diabetes type 1

Abstract: Ocena stężenia wybranych markerów procesu miażdżycowego u dzieci i młodzieży z cukrzycą typu 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…During the next few years of their diabetes children and adolescents were seen to present with mild inflammatory state, but when duration of diabetes was longer than 5 years chronic inflammatory state with detectable markers developed [40, 47]. Studies by other authors did not reveal any difference in hsCRP levels in patients with duration of diabetes up to 1 year versus T1DM patients with history of diabetes longer than 1 year either [47, 48]. On the other hand, lack of difference in hsCRP levels and lack of correlation with serum IL12 levels may suggest “good metabolic memory” and persistence of stable inflammatory state [49, 50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the next few years of their diabetes children and adolescents were seen to present with mild inflammatory state, but when duration of diabetes was longer than 5 years chronic inflammatory state with detectable markers developed [40, 47]. Studies by other authors did not reveal any difference in hsCRP levels in patients with duration of diabetes up to 1 year versus T1DM patients with history of diabetes longer than 1 year either [47, 48]. On the other hand, lack of difference in hsCRP levels and lack of correlation with serum IL12 levels may suggest “good metabolic memory” and persistence of stable inflammatory state [49, 50].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, lack of difference in hsCRP levels and lack of correlation with serum IL12 levels may suggest “good metabolic memory” and persistence of stable inflammatory state [49, 50]. Chronic hyperglycaemia is accompanied by inflammatory state in patients with longer duration of type 1 diabetes [47, 48]. In our study the subgroup of children and adolescents with the shortest duration of diabetes, up to 2 years, showed good metabolic control with HbA1c levels 6.9 ± 0.6%.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in a group of 125 patients with type 1 diabetes revealed that proinflammatory cytokines IL-6, TNF-α, and IFN-γ as well as anti-inflammatory cytokine IL-10 showed a mutual positive correlation, which may suggest their supplementary activity in the context of the emergence and progression of vascular complications in diabetics [81]. A study conducted in Poland in a group of 71 children (aged 7-17) with type 1 diabetes demonstrated that from the first years of the disease, elevated concentrations of inflammation markers (hsCRP, IL-6, IL-1) could be observed compared to healthy children [75]. In turn, a Turkish study conducted among children with type 1 diabetes confirmed the activation of a systemic inflammatory process already in the early stages of the disease, which may indicate ongoing destruction of β cells, whereas as the disease continues to progress, the levels of IL-1β, IL-2, IL-6, and TNF-α confirm continuous activation of proinflammatory factors, even in late stages of diabetes [79].…”
Section: Inflammationmentioning
confidence: 95%
“…Hyperglycemia activates the apoptosis of β cells due to the activity of cytokines produced by the subpopulation of Th1 lymphocytes: INFγ, IL-2, and 1IL-18; interleukins produced by macrophages: IL-1, IL-6, IL-8, and IL-12; and TNFα. It is believed that cytokines released by the subpopulation of Th2 lymphocytes: IL-4, IL-5, IL-10, and IL-13 act protectively, inhibiting the activity of Th1 lymphocytes, which is particularly apparent in early stages of the disease [74,75]. In response to inflammation, blood serum proteins are produced that act as mediators of the ongoing inflammatory process, mostly high sensitivity c-reactive protein hsCRP and interleukins [75].…”
Section: Inflammationmentioning
confidence: 99%
See 1 more Smart Citation